Single-Dose and Steady-State Pharmacokinetics of Tenofovir Disoproxil Fumarate in Human Immunodeficiency Virus-Infected Children - Hazra, Rohan (American Society for Microbiology, 2004)
Tenofovir disoproxil fumarate (DF) is a potent nucleotide analog reverse transcriptase inhibitor approved for the treatment of human immunodeficiency virus (HIV)-infected adults. The single-dose and steady-state pharmacokinetics of tenofovir were evaluated following administration of tenofovir DF in treatment-experienced HIV-infected children requiring a change in antiretroviral therapy. Using increments of tenofovir DF 75-mg tablets, the target dose was 175 mg/m(2); the median administered dose was 208 mg/m(2). Single-dose pharmacokinetics were evaluated in 18 subjects, and the geometric mean area under the concentration-time curve from 0 h to ∞ (AUC(0-∞)) was 2,150 ng · h/ml and the geometric mean maximum concentration (C(max)) was 266 ng/ml. Subsequently, other antiretrovirals were added to each patient's regimen based upon treatment history and baseline viral resistance results. Steady-state pharmacokinetics were evaluated in 16 subjects at week 4. The steady-state, geometric mean AUC for the 24-h dosing interval was 2,920 ng · h/ml and was significantly higher than the AUC(0-∞) after the first dose (P = 0.0004). The geometric mean C(max) at steady state was 302 ng/ml. Tenofovir DF was generally very well tolerated. Steady-state tenofovir exposures in children receiving tenofovir DF-containing combination antiretroviral therapy approached values seen in HIV-infected adults (AUC, ∼3,000 ng · h/ml; C(max), ∼300 ng/ml) treated with tenofovir DF at 300 mg.